Controle genético da qualidade fisiológica das sementes associado à rápida cobertura do solo na cultura do feijoeiro - Santos, Astúrio Silva dos (2016)
Among the factors that interfere with the production of bean crops are the weeds that compete for water, light, nutrients and space, decreasing productivity and increasing production cost. They also hinder harvest, causing losses and contamination, reducing the quality and depreciating the product. Using preventive control, it is possible to obtain cultivars that allow fast soil coverage, mitigating this competition. This work was conducted to obtain information regarding the genetic control of morphological and physiological traits of bean seeds, in order to contribute for obtaining line with faster soil coverage. For this, six parental plants, representing lines Paraná, Amarelinho, Goiano Precoce, Eriparsa, MAII-22 and Madrepérola, were crossed according to a diallel scheme. Using seeds from generation F4, the following physiological traits were evaluated: standard germination test; accelerated aging; emergence percentage and emergence speed index in seedbed. Using the means of parents and hybrids, we conducted the diallel analysis according to Griffing (1956) method II. We verified that the heterosis estimates presented low magnitude for the morphological traits of the seeds, while the opposite occurred for the traits associated to physiological quality. In conclusion, the dominance allele interaction is important only for physiological traits. The association between morphological and physiological traits is small and negative. Parents of larger seeds, which normally present larger leaves, present ed lower germination vigor than those with smaller seeds. Associating higher germination vigor with higher initial vegetative growth must be small, which may hinder the selection of bean lines with faster soil coverage.